What is Most Difficult in a Teacher's Job from the Perspective of Teachers, Students and Parents? - Plavšić, Marlena; Diković, Marina (Revija za elementarno izobraževanje, 2022)
The purpose of this research lies on the fact that although teacher’s job is generally considered to be satisfactory, some of its aspects are perceived as difficult. In this qualitative study, conducted in Croatia, 158 students, 78 teachers and 148 parents were interviewed. The most frequently listed difficult aspects of teacher’s job were keeping discipline, transferring knowledge, motivating students, working with problematic children, communicating well with students, adjusting to students, assessing students’ knowledge realistically, and working with parents. Answers varied slightly between participants, between primary and secondary schools, as well as depending on the length of teaching careers.
Keywords: parents, students, teachers’ profession, teaching